ЕРКІН ЭКОНОМИКАЛЫҚ АЙМАҚТАРДЫ ҚАЛЫПТАСТЫРУДЫҢ ТЕОРИЯЛЫҚ АЛҒЫШАРТТАРЫ МЕН ПРАКТИКАЛЫҚ ШАРТТАРЫ - Zh. P. Kozhambekov (Экономика: стратегия и практика, 2018)
The article is devoted to the formation of FEZs, their classification and criteria for the need for their functioning. It is proved that modern FEZs, absorbed a long way of development of their predecessors, no doubt, filled with the latest export-production content and business experience. Their creation and establishment is aimed at liberalization and active foreign economic activity. The economies of such zones are highly open to the world market, and customs and tax regimes are favourable to domestic and foreign investment. International corporations in search of favorable conditions for their commercial activities consider FEZs as profitable economic structures and associate with them the most important areas of their activities. The relevance of the study is associated with the progressive dynamics of this process in Kazakhstan. The use of FEZs should provide favorable opportunities for the development of the national economy and export-oriented production, providing a full cycle of production of high-tech finished products of strategically important sectors of the national economy with high added value. It is noted that at the present moment the FEZ is a phenomenal formation that in the beginning of XXI century became an important factor of the world economy and represent a kind of “commercial centers” that accelerate global trade and stimulating foreign trade.